The Cultures of Globalization - Miyoshi, Masao; Jameson, Fredric (Book collections on Project MUSE., 1998)
A pervasive force that evades easy analysis, globalization has come to represent the export and import of culture, the speed and intensity of which has increased to unprecedented levels in recent years. The Cultures of Globalization presents an international panel of intellectuals who consider the process of globalization as it concerns the transformation of the economic into the cultural and vice versa; the rise of consumer culture around the world; the production and cancellation of forms of subjectivity; and the challenges it presents to national identity, local culture, and traditional forms of everyday life. Discussing overlapping themes of transnational consequence, the contributors to this volume describe how the global character of technology, communication networks, consumer culture, intellectual discourse, the arts, and mass entertainment have all been affected by recent worldwide trends. Appropriate to such diversity of material, the authors approach their topics from a variety of theoretical perspectives, including those of linguistics, sociology, economics, anthropology, and the law. Essays examine such topics as free trade, capitalism, the North and South, Eurocentrism, language migration, art and cinema, social fragmentation, sovereignty and nationhood, higher education, environmental justice, wealth and poverty, transnational corporations, and global culture. Bridging the spheres of economic, political, and cultural inquiry, The Cultures of Globalization offers crucial insights into many of the most significant changes occurring in today?s world. Contributors. Noam Chomsky, Ioan Davies, Manthia Diawara, Enrique Dussel, David Harvey, Sherif Hetata, Fredric Jameson, Geeta Kapur, Liu Kang, Joan Martinez-Alier, Masao Miyoshi, Walter D. Mignolo, Alberto Moreiras, Paik Nak-chung, Leslie Sklair, Subramani, Barbara Trent.